Analysis of the disease burden of ischemic heart disease attributable to dietary factors in china from 1990 to 2017 - Guo-Xiang TIAN; Zhu SUN; Yun-Tao WU; Wei ZHANG; Wan-Lin WEI (Yixue xinzhi zazhi)
Objective To study the disease burden of ischemic heart disease (IHD) attributable to dietary factors in China from 1990 to 2017.Methods Data from the Global Disease Burden 2017 (GBD 2017) were used to analyze the changes of disability adjusted life years (DALY) of IHD attributable to dietary factors by ages and genders in China. Joinpoint model was used to evaluate the temporal trend of disease burden.Results The crude DALY rate of IHD attributable to dietary factors increased by 83.46% and the standardized DALY rate increased by 0.8% from 1990 to 2017. The crude DALY rate of males increased by 2.8% per year (95% CI: 2.6, 3.1) (P< 0.05) and that of females by 2.4% per year (2.2, 2.7) (P< 0.05). The standardized DALY rate of males increased by 0.6% per year (0.4, 0.8) (P< 0.05), while that of females decreased by 3.4% per year (-3.6, -3.2) (P< 0.05). The DALY rate of IHD attributable to dietary factors gradually increased with age, with the highest rate in people over 80 years old. The top five dietary risk factors of IHD burden in 2017 were diet high in sodium, diet low in nuts and seeds, diet low in whole grains, diet low in fruits and fiber. The disease burden caused by diet high in processed meat and sugar-sweetened beverages, diet low in legumes and diet high in sodium were still rising.Conclusion Dietary factors are the most important risk factors for IHD. The disease burden of IHD caused by dietary factors was heavy in China. The elderly and men were the key groups of disease burden, so effective interventions should be taken for these groups.